ANALISIS PERBEDAAN RATA-RATA TRADING VOLUME ACTIVITY SAHAM SEBELUM DAN SESUDAH PEMILU PRESIDEN DAN WAKIL PRESIDEN TAHUN 2014 (Event Study Pada Saham LQ-45 Di Bursa Efek Indonesia Periode 29 Juni - 19 Juli 2014) - Indra Saputra (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2016)
Abstract, This purpose of this research was to find out whether there are differences in average trading volume activity shares before and after the election of the president and vice president of the year 2014 (event study on shares LQ – 45 in Indonesia Stock Echange period 29 June - 19 July 2014). The sample drawn by purposive sampling and fulfill sample selection criterion. This research was conducted to examine and analyze the differences in the average stock trading volume activity before and after the election of president and vice president in 2014 in the capital market. Methods of data analysis using paired sample t test. The results of this research indicate that the result of paired samples t-test average stock trading volume activity there is no difference in the LQ-45 before and after the elections for president and vice president in 2014.